PENERAPAN ASUHAN KEPERAWATAN PADA USIA LANSIA DENGAN MASALAH HIPERTENSI MELALUI INTERVENSI BRISK WALKING EXERCISE DI RT 009 RW 002 PONDOK LABU JAKARTA SELATAN - Sukmawati Dewi (2022)
Hypertension was defined as a sustained increase in systolic blood pressure of at least 140 mmHg and diastolic blood pressure of at least 90 mmHg. Brisk walking exercise is a type of aerobic exercise that combines routine activity training with a brisk walking approach for 20-30 minutes at a speed of 4-6 km/hour in hypertensive individuals. The purpose of this nursing care application is to determine the effect of brisk walking exercise intervention on reducing blood pressure. The brisk walking exercise was applied to 2 patients, namely the main managed patient and the resume patient. The application of brisk walking exercise therapy was carried out in 3 meetings with a meeting duration of 20-30 minutes at a speed of 4-6 km/hour. The results of the implementation of brisk walking exercise in primary managed patients showed a decrease in blood pressure from 160/100 mmHg to 150/90 mmHg and in resume patients there was a decrease in blood pressure from 160/110 mmHg to 160/90 mmHg. These results indicate that brisk walking exercise is proven to reduce blood pressure. Community nurses are advised to use this therapy as a complementary therapy in lowering blood pressure.